Contributions to forest and land fire prevention: a case of how the DMPA program strategic approaches in Riau Province / Nurul Huda, Salyani Osman and Azmuddin Ibrahim - Huda, Nurul; Osman, Salyani; Ibrahim, Azmuddin (Center for Islamic Philanthropy and Social Finance (CIPSF), 2021)
Riau Province is one of eight provinces in Indonesia that are always faced with forest and land fires every year which impact health, economy, education, socio-culture, tourism, and the environment in Riau Province. This paper aims to discuss how the Desa Makmur Peduli Api (DMPA) Program's contribution was form ed by the Asia Pulp & Paper (APP) Sinar Mas company to minimize forest and land fires in Riau Province, especially fo r forests and land adjacent to APP Sinar Mas's concession areas. This article uses a case study as a research design. Case study research allows fo r an in-depth review of new or obscure phenomena while maintaining real-life events' holistic and meaningful characteristics. In this paper, the authors interviewed community leaders and activists of the Village of Makmur Peduli Api (DMPA) to explore the contribution of DMPA in preventing and overcoming forest and land fires in Riau Province. This paper's findings are that DMPA contributes to the prevention and control of Forest and Land Fires in Riau Province by the following methods: (1) changing the mindset and behavior of the community in clearing land by not burning. (2) Changing the people's mindset from initially cultivating tree crops to horticulture and other businesses such as fisheries (3). Increasing the community's economy.This paper concludes that Desa Makmur Peduli Api (DMPA) contributes to the prevention and control of forest and land fires in the Riau Province.